Regulation of parental investment in the Antarctic petrel Thalassoica antarctica: an exchange experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Polar Biology, 1995)
An experiment was conducted on the Antarctic petrel to test whether the parents were able to respond to changes in food demand of their offspring. Two experimental groups were formed by replacing eight 20-day-old chicks with 10-day-old chicks, and vice versa. The growth rate of chicks in the experimental groups was compared with that in two control groups with chicks of known age. The growth rate of 10-day-old chicks in the nests of parents which initially had 20-day-old chicks did not differ significantly from that in their respective control groups. This indicates that those parents were able to raise a new young nestling, despite having already raised another chick from hatching to 20 days. However, the 20-day-old chicks placed in nests with 10-day-old chicks had a significantly lower growth rate than their control group. Feeding rate per day and nest did not differ significantly among any of the groups. This suggests that the observed difference in growth rate between 20-day-old chicks is related to a lower amount of food delivered per visit to experimental chicks. Thus, in the Antarctic petrel, the feeding rate apparently is not regulated by the status of the chick, but by the parents' ability to gather food or willingness to provide food for the chicks.
Keywords: Dronning Maud Land; NARE 1989/90; fugler; ornitologi; petreller; zoologi